ASL Phonological Fluency: How Do Deaf Signers Retrieve and Produce Signs?. (15th December 2022) - Beal, Jennifer S; Bowman, Sarah
Abstract: Researchers have focused on how deaf signing children acquire and use American Sign Language (ASL). One sub-skill of ASL proficiency is ASL phonology. This includes the ability to isolate and manipulate parameters within signs (i.e., handshape, location, and movement). Expressively, signed language phonological fluency tasks have investigated signers' abilities to produce signs given handshape constraints. We expanded the handshape task with the addition of sign production for two given locations with deaf adults and students. We also investigated how adjacent signs were recalled and produced within semantic and phonological clusters. Deaf adults frequently recalled signs with semantic connections and shared location. Students did the same, although shared handshape also facilitated their sign production. Finally, we present implications for ASL instruction with deaf students.